1998
DOI: 10.1046/j.1365-2281.1998.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a sympathetic activation by lower body negative pressure on glucose and lipid metabolism

Abstract: The effects of a sympathetic activation elicited by a lower body negative pressure (LBNP) (at -15 mmHg for 75 min) were assessed in 7 healthy subjects on two occasions: (i) in post-absorptive conditions, and (ii) during glucose infusion (22.2 mumol kg-1 min-1). LBNP increased plasma norepinephrine concentration and heart rate. It did not alter whole-body glucose metabolism (measured with [6,6-2H]glucose) and glycerol turnover (measured with [1,1,2,3,3-2H]glycerol). Interstitial glycerol concentrations were mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A role for sympathetic outflow to skeletal muscle in human obesity has been proposed (Spraul et al 1993; Snitker et al 1998), but this sympathetic subdivision modulates glycerol concentrations in muscle and not in subcutaneous fat tissue (Henry et al 1998). Our present demonstration of a neural modulation of subcutaneous fat tissue metabolism mediated via cutaneous nerve fascicles, in conjunction with the well established fact that sympathetic activity at rest and in response to various stimuli differs substantially between fascicles innervating muscle and skin (Vallbo et al 1979; Wallin & Elam, 1997 a ), indicates that a sympathetically mediated mobilization of fat stores may be highly differentiated and may involve different tissues depending on the type of stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…A role for sympathetic outflow to skeletal muscle in human obesity has been proposed (Spraul et al 1993; Snitker et al 1998), but this sympathetic subdivision modulates glycerol concentrations in muscle and not in subcutaneous fat tissue (Henry et al 1998). Our present demonstration of a neural modulation of subcutaneous fat tissue metabolism mediated via cutaneous nerve fascicles, in conjunction with the well established fact that sympathetic activity at rest and in response to various stimuli differs substantially between fascicles innervating muscle and skin (Vallbo et al 1979; Wallin & Elam, 1997 a ), indicates that a sympathetically mediated mobilization of fat stores may be highly differentiated and may involve different tissues depending on the type of stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…In these previous studies, not only the stimulation of SNS, as documented by microneurography of the lateral peroneal nerve, but also the vasodilatory effects normally elicited by these manoeuvers were inhibited by dexamethasone. A role of the SNS in these forms of insulin resistance appears supported by the observations that noradrenergic activation elicited by a lower body negative pressure reduces acutely insulin-mediated glucose disposal (Lembo et al, 1994;Henry et al, 1998). This indicates that mental stress activates SNS through different central pathways than those stimulated by insulin, alcohol and hypoglycaemia.…”
Section: Discussionmentioning
confidence: 90%
“…A similar reduction in insulin sensitivity is seen during the administration of the α-adrenergic agonist norepinephrine [20] suggesting that the reduction in insulin sensitivity may be mediated by α1-adrenergic receptors [25]. However, other studies have not found whole body glucose uptake to be affected by sympathetic stimulation [12]. Some prospective studies suggest that sympathetic activation precedes insulin resistance: norepinephrine levels in men predict insulin levels 10 years later [24] and greater sympathetic reactivity is associated with the development of insulin resistance many years later [5].…”
Section: Discussionmentioning
confidence: 91%